ANALISIS PENGEMBANGAN AGRIBISNIS KOMODITAS UNGGULAN DI KABUPATEN LAMPUNG TENGAH - Didin Dianarafah; Assad Saifullah Harahap; Ansyori Ansyori; Elly Rosnarita (Jurnal WACANA PERTANIAN, 2021)
The development of agribusiness is important because the added value of all series of agricultural production is created in the subsystem of cultivation, marketing and processing, namely rural agro-industry can be a transition phase towards structural transformation of agriculture to real agricultural production. The development of regional commodities must be based on the comparative advantage of the location, thus agricultural products with special characteristics must have a better development orientation and proper management to achieve maximum efficiency. This study aims to determine the priority commodities that are prioritized to be developed and to formulate directions for the development of superior commodity agribusiness in Central Lampung Regency. The method used is a case study method with a case unit selected intentionally (purposively) in Central Lampung. The data used in this study are primary data and secondary data. Data analysis techniques include determining: superior commodities; priority commodities, and directions for developing superior commodities. The conclusion of this study is that the main base commodities in Central Lampung Regency are rice (R/C ratio 11.36), cassava (R/C ratio 5.67) and corn (R/C ratio 4.24). The directions for developing superior commodities are; land allocation for rice plants is 54,218 ha with development centers in Trimurjo, Punggur, Kota Gajah, Padang Ratu, Seputih Agung, Terbanggi Besar, Seputih Mataram, and Way Seputih sub-districts, while for corn an area of 41,271 ha with development centers in Gunungsugih District, Seputih Raman, and Seputih Banyak and for cassava covering an area of 38,852 ha with development centers in Anak Tuha, Way Pengubuan and Rumbia sub-districts.